Effect of Ataluren on dystrophin mutations. Issue 12 (28th April 2020) - Berger, Joachim; Li, Mei; Berger, Silke; Meilak, Michelle; Rientjes, Jeanette; Currie, Peter D.
Abstract: Duchenne muscular dystrophy is a severe muscle wasting disease caused by mutations in the dystrophin gene ( dmd ). Ataluren has been approved by the European Medicines Agency for treatment of Duchenne muscular dystrophy. Ataluren has been reported to promote ribosomal read‐through of premature stop codons, leading to restoration of full‐length dystrophin protein. However, the mechanism of Ataluren action has not been fully described. To evaluate the efficacy of Ataluren on all three premature stop codons featuring different termination strengths (UAA > UAG > UGA), novel dystrophin‐deficient zebrafish were generated. Pathological assessment of the muscle by birefringence quantification, a tool to directly measure muscle integrity, did not reveal a significant effect of Ataluren on any of the analysed dystrophin‐deficient mutants at 3 days after fertilization. Functional analysis of the musculature at 6 days after fertilization by direct measurement of the generated force revealed a significant improvement by Ataluren only for the UAA‐carrying mutant dmd ta222a . Interestingly however, all other analysed dystrophin‐deficient mutants were not affected by Ataluren, including the dmd pc3 and dmd pc2 mutants that harbour weaker premature stop codons UAG and UGA, respectively. These in vivo results contradict reported in vitro data on Ataluren efficacy, suggesting that Ataluren might not promote read‐through of premature stop codons. In addition, Ataluren had no effect on dystrophin transcript levels, but mild adverse effects on wild‐type larvae were identified. Further assessment of N‐terminally truncated dystrophin opened the possibility of Ataluren promoting alternative translation codons within dystrophin, thereby potentially shifting the patient cohort applicable for Ataluren.